2008
DOI: 10.1021/cm800597k
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Aminopropyl-Functionalized Hybrid Thin Films with Modulable Surface and Environment-Responsive Behavior

Abstract: A first study of the behavior of amino functions in mesoporous hybrid thin films M 1-x (Si-(CH 2 ) 3 NH 2 ) x O 2-x/2 (M ) Si, Ti, Zr; 0.05 e x e 0.2) with accessible Im3 j m-or Fm3 j m-derived pore mesostructures is presented. An XPS study of surface nitrogen species shows two different sites corresponding to amino and ammonium groups. The ratio of these species changes with pH and is related to the nature of M, suggesting that the interaction between the organic functions and the surface M-OH groups can be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
96
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 57 publications
6
96
0
7
Order By: Relevance
“…The enhancement of the small IR band at~695 cm − 1 was considered to be partially from primary amine bending vibration which could also be attributed to Si-CH 2 bond [31,32]. Increase in the C-H stretching (generally between 2800-3000 cm − 1 and specifically at~2934 cm − 1 ), appearance of bending vibrations (δ CH2 at~1470, 1448 and 1410 cm −1 ), weakening of Si-OH wide stretching band (at~3440 cm −1 ) and bending vibration (δ OH at~1630 cm −1 and~960 cm −1 ), could all be indications of considerable removal of surface silanol groups due to higher number of amine groups loaded by grafting than those of thiol groups obtained through co-condensation [32][33][34][35][36][37].…”
Section: Structural and Functional Properties Of Mesoporous Adsorbentsmentioning
confidence: 98%
“…The enhancement of the small IR band at~695 cm − 1 was considered to be partially from primary amine bending vibration which could also be attributed to Si-CH 2 bond [31,32]. Increase in the C-H stretching (generally between 2800-3000 cm − 1 and specifically at~2934 cm − 1 ), appearance of bending vibrations (δ CH2 at~1470, 1448 and 1410 cm −1 ), weakening of Si-OH wide stretching band (at~3440 cm −1 ) and bending vibration (δ OH at~1630 cm −1 and~960 cm −1 ), could all be indications of considerable removal of surface silanol groups due to higher number of amine groups loaded by grafting than those of thiol groups obtained through co-condensation [32][33][34][35][36][37].…”
Section: Structural and Functional Properties Of Mesoporous Adsorbentsmentioning
confidence: 98%
“…[6,20,22,25,26] Mesoporous silica nanoparticles (MSNs) are ac lass of OMSs that are particularly importanti nt he field of nanomedicine. [19,[28][29][30][31][32][33][34] It can be obtained from organosilanes such as 3-aminopropyltriethoxysilane (APTS, the most commonly employed), 3-aminopropylmethyldiethoxysilane and 3-aminopropyl dimethylethox-ysilane. [22,27] In the variousa pplications mentioned above, the aminopropylf unctional group plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…[42] This functionalisation is usually aimed at optimising the interaction with the desired target adsorptive: CO 2 in carbon capture and storagea pplications, pollutantsi ne nvironmental applications, reactants in catalysis, drugs in nanomedicine and so forth. [28,32,33,40,46,47] Moreover,B litz et al recently showed that surfaceamino groups can have acatalytic effect on the reactivity of vicinal silanols. [30,41] The surface chemistry of amino-functionalised silica materials can be quite complex, owing to the interactions between amino and silanol groups,w hich result in av ariety of hydrogen-bonded structures and in the formation of NH 3 + /SiO À couples.…”
Section: Introductionmentioning
confidence: 99%
“…The selected method clearly affects the textural and chemical properties of the final hybrid silica material and thus its performance as adsorbent [17]. This is mainly because when co-condensation is used, up to 80 % of the organic groups may be incorporated within the walls of the mesoporous matrix and therefore they are inaccessible for the adsorbate [18]. When the post-synthesis method is chosen, a complete exposure of the organic functions can be achieved [19].…”
Section: Introductionmentioning
confidence: 99%